2020
DOI: 10.1080/08854726.2020.1861535
|View full text |Cite
|
Sign up to set email alerts
|

What organizational and business models underlie the provision of spiritual care in healthcare organizations? An initial description and analysis

Abstract: Two-thirds of American hospitals have chaplains. This article explores the organizational and business models that underlie how chaplains are integrated into hospitals. Based on interviews with 14 chaplain managers and the 11 healthcare executives to whom they report at 18 hospitals in 9 systems, we identify three central findings. First, there is significant variation in how spiritual care programs are staffed and integrated into their hospitals. Second, executives and chaplain managers see the value of chapl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…These findings support those of Antoine et al (2021, 2022), suggesting that hospital leaders vary in how they staff and integrate chaplaincy departments. However, while these researchers found that the 11 hospital leaders surveyed appeared to see chaplains in positive ways (Antoine et al, 2021, 2022), the current data suggest that challenges can also arise in these relationships, and that hospital leaders may not always be wholly and optimally supportive, but may at times be less than fully supportive, and can be affected by various contextual factors. These data suggest, too, how VA hospitals, for instance, may support chaplains relatively more than many other secular institutions, due to federal policy mandates.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…These findings support those of Antoine et al (2021, 2022), suggesting that hospital leaders vary in how they staff and integrate chaplaincy departments. However, while these researchers found that the 11 hospital leaders surveyed appeared to see chaplains in positive ways (Antoine et al, 2021, 2022), the current data suggest that challenges can also arise in these relationships, and that hospital leaders may not always be wholly and optimally supportive, but may at times be less than fully supportive, and can be affected by various contextual factors. These data suggest, too, how VA hospitals, for instance, may support chaplains relatively more than many other secular institutions, due to federal policy mandates.…”
Section: Discussionsupporting
confidence: 81%
“…It is unclear, for instance, whether factors such as hospital affiliation may affect not only the presence or absence of chaplains, but also what these professionals do, how they are organized, and fill and see their roles and how the professionals, patients, and families perceive these spiritual care providers. Antoine et al (2021Antoine et al ( , 2022 interviewed 11 healthcare leaders (e.g., the director of patient relations and chief nursing officer) and 14 chaplain managers, and reported that the healthcare leaders saw chaplains' value in supporting staff in tragic situations and organizational change, and felt they supported chaplains, despite financial strains on the institution (Antoine et al, 2021(Antoine et al, , 2022. These institutions varied in how they staffed and integrated spiritual care programs, but saw the value of chaplains in helping staff and patients (through providing quality care, responding to patient and staff needs and having experience in the complex hospital milieu) (Antoine et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In practice, the organization of Spiritual Care staffing appears almost as varied as those settings in which the care is provided (Antoine et al, 2020). One traditional approach that appears commonly applied relates to a departmental structure with identified leadership supporting care direction and organizing staffing/facility coverage (Newberry, 2009).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Cadge's (2012) observation about the importance of spiritual care managers' becoming "familiar with the language and priorities of [their] healthcare system" highlights the importance of the relationship between spiritual care managers and the executives to whom they report (p. 119). Antoine et al (2020Antoine et al ( , 2021 interviewed 11 healthcare executives before the COVID-19 pandemic to learn what they knew about and valued in the spiritual care programs in their organizations. They found the executives valued the support that chaplains provided to healthcare colleagues in tragic situations and during organizational change.…”
mentioning
confidence: 99%